Assessing sustainment of health worker outcomes beyond program end: Evaluation results from an infant and young child feeding intervention in Bangladesh - Moucheraud, Corrina; Epstein, Adrienne; Sarma, Haribondhu; Kim, Sunny S.; Nguyen, Phuong Hong; Rahman, Mahfuzur; Tariquijaman, Md.; Glenn, Jeffrey; Payán, Denise D.; Menon, Purnima; Bossert, Thomas J. (Frontiers in Health Services, 2023)
Introduction: Alive and Thrive (A&T) implemented infant and young child feeding (IYCF) interventions in Bangladesh. We examine the sustained impacts on health workers’ IYCF knowledge, service delivery, job satisfaction, and job readiness three years after the program’s conclusion. Methods: We use data from a cluster-randomized controlled trial design, including repeated cross-sectional surveys with health workers in 2010 (baseline, n=290), 2014 (endline, n=511) and 2017 (post-endline, n=600). The primary outcome is quality of IYCF service delivery (number of IYCF messages reportedly communicated during counseling); intermediate outcomes are IYCF knowledge, job satisfaction, and job readiness. We also assess the role of hypothesized modifiers of program sustainment, i.e. activities of the program: comprehensiveness of refresher trainings and receipt of financial incentives. Multivariable difference-in-difference linear regression models, including worker characteristic covariates and adjusted for clustering at the survey sampling level, are used to compare differences between groups (intervention versus comparison areas) and over time (baseline, endline, post-endline). Results: At endline, health workers in intervention areas discussed significantly more IYCF topics than those in comparison areas (4.9 versus 4.0 topics, p<0.001), but levels decreased and the post-endline gap was no longer significant (4.0 versus 3.3 topics, p=0.067). Comprehensive refresher trainings were protective against deterioration in service delivery. Between baseline and endline, the intervention increased health workers’ knowledge (3.5-point increase in knowledge scores in intervention areas, versus 1.5-point increase in comparison areas, p<0.0001); and this improvement persisted to post-endline, suggesting a sustained program effect on knowledge. Job satisfaction and readiness both saw improvements among workers in intervention areas during the project period (baseline to endline) but regressed to a similar level as comparison areas by post-endline. Discussion: Our study showed sustained impact on health workers’ knowledge, but not job satisfaction or job readiness—and, critically, no sustained program effect on service delivery. Programs of limited duration may seek to assess the status of and invest in protective factors identified in this study (e.g., refresher trainings) to encourage sustained impact of improved service delivery. Studies should also prioritize collecting post-endline data to empirically test and refine concepts of sustainment.